Modelling sodium requirements of athletes across a variety of exercise scenarios - Identifying when to test and target, or season to taste - McCubbin, A. J. (European Journal of Sport Science, 2023)
Evidence suggests the focus for sodium replacement during exercise should be maintenance of plasma sodium concentration ([Na+]plasma) for any given total body water (TBW) volume. The sodium intake to achieve stable [Na+]plasma given known fluid and electrolyte intakes and losses can be mathematically estimated. Therefore the aim of this investigation was to model sodium requirements of athletes during exercise, observing the influence of sweat rate, exercise duration, body mass, baseline [Na+]plasma and sweat potassium [K+]sweat, and relevance to competition (soccer, elite marathon, and 160 km ultramarathon running). Models were constructed across a range of sweat sodium concentrations ([Na+]sweat) (20-80 mmol/L), sweat rates (0.5-2.5 L/h) and fluid replacement (10-90% of losses). In the competition-specific scenarios, fluid replacement was calculated to achieve 2% TBW losses. Sodium requirements were driven by fluid replacement (% of losses) and [Na+]sweat, with minimal or no influence of other variables. Replacing sodium was unnecessary in all realistic scenarios modelled for a soccer match and elite marathon. In contrast, the 160 km ultramarathon required =47% sodium replacement when [Na+]sweat was =40 mmol/L and >80% of fluid losses were replaced. In conclusion, sodium requirements to maintain stable [Na+]plasma during exercise depend on both the proportion of fluid losses replaced, and [Na+]sweat. Only when prolonged exercise is coupled with aggressive fluid replacement (>80%) and whole body [Na+]sweat =40 mmol/L does sweat composition testing and significant, targeted sodium replacement appear necessary.